IS THERE REFUGE FOR PEOPLE WITH DISABILITIES WITHIN THE 1951 CONVENTION RELATING TO THE STATUS OF REFUGEES? - Parekh, Gillian (Critical Disability Discourses, 2009)
Forms of oppression affecting specific social groups such as women and people with disabilities are demanding international address and rights protection for those deemed persecuted and oppressed. In 1951, the United Nations developed the Refugee Convention, which has remained largely unchanged since its inception and has neglected to incorporate protection of newly recognized social groups. Recently, Canadian immigration and refugee laws have begun to develop legislation to address these issues, specifically in regards to gender-related persecution. By examining Canadian federal amendments to refugee and immigration law and United Nations documents developed by the Office of the United Nations High Commissioner for Refugees, this paper will argue that an amendment protecting persons facing disability-related oppression is in keeping with current Canadian values and means. Supportive documents emphasize the legal benefits of people with disabilities identifying as members of a unique social group that would then require the recognition of the widespread international incidence of disability-specific oppression and persecution. Implementation of a disability-related amendment to the 1951 Refugee Convention would not only create asylum opportunities for those fleeing regimes that practise or propagate disability persecution and oppression, but would create further awareness of the international community's intolerance of such practices.